Branding dan Pemasaran Produk Halal UKM Berbasis Persepsi Konsumen - Rasnawati, Rasnawati; Sirajuddin, Sirajuddin; Awaluddin, Murtiadi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines consumer perceptions of halal product branding and marketing for Small and Medium Enterprises (SMEs) in South Sulawesi, identifying the challenges faced by SMEs in marketing halal products. The main issue raised is consumers' lack of understanding of the added value and advantages of halal products and their impact on purchasing decisions. The purpose of this study is to analyze consumer perceptions and explore the factors influencing halal product purchasing decisions. The approach used was qualitative with descriptive methods, and data were obtained through in-depth interviews, observation, and documentation. The research informants consisted of halal product branding and marketing personnel of Small and Medium Enterprises (SMEs) in South Sulawesi. The results indicate that trust in halal certification, product quality, and effective marketing strategies contribute to consumer purchasing decisions. The implications of this study are crucial for SMEs in formulating more effective marketing strategies. This study recommends that SMEs utilize social media and digital platforms to increase product visibility and educate consumers about the benefits of halal products. The results are expected to provide valuable insights for the development of the halal industry in South Sulawesi.